A comprehensive guide to the AFP cases in medicine and surgery - Abdulhussein, Dalia (World Scientific, 2021)
"The authors are three recent graduates from Imperial College London who have all secure their first choice AFP jobs in a highly competitive programme in London. During their time in preparing for the interview process, they found that resources were limited in the information the resources conveyed and guidance was based on information passed down from colleagues. Hence, the aim of this book is to not only explain the application process but also provides prospective applicants with a useful workbook presenting several mock scenarios to work through. The interview forms the biggest proportion of the marks allocated to a candidate application and hence is the key determinant in securing a job."--